Learning web development with React and Bootstrap : build real-time responsive web apps using React and Bootstrap - Singh, Harmeet; Bhatt, Mehul (Packt Publishing, 2016)
Build real-time responsive web apps using React and Bootstrap About This Book Showcase the power of React-Bootstrap through real-world examples Explore the benefits of integrating React with various frameworks and APIs See the benefits of using the latest frameworks to make your web development experience enchanting Who This Book Is For This book is for anybody who is interested in modern web development and has intermediate knowledge of HTML, CSS, and JavaScript. Basic knowledge of any JavaScript MVC framework would also be helpful. What You Will Learn See how to integrate Bootstrap with React Explore the Redux architecture and understand its benefits Build a custom responsive theme with React-Bootstrap components Easily interact with DOM on your web browser Appreciate the advantages of using JSX Get acquainted with the various routing methods in React Integrate external APIs into React In Detail Bootstrap is one of the most popular front-end frameworks, and integrating it with React allows web developers to write much cleaner code. This book will help you gain a thorough understanding of the Bootstrap framework and show you how to build impressive web apps. In this book, you will get an overview of the features of Bootstrap and ReactJS, along with the integration of React-Bootstrap components with ReactJS. You will understand the benefits of using JSX and the Redux architecture. The server-side rendering of React will also be shown. All the concepts are explained by developing real-world examples. By the end of this book, you will be equipped to create responsive web applications using Bootstrap style and React-Bootstrap components with ReactJS, and will have an insight into the best practices. Style and approach The mission is to help you make a live and fully-responsive web application using React-Bootstrap with hands-on examples and step-by-step instructions. This book is linear as well as progressive, so every chapter builds upon the knowledge gained in the last.